Antibody response to rotavirus A and C in gilts and their piglets after prenatal natural planned exposure - Kumar, Deepak (Kansas State University, 2022)
Rotaviruses (RVs) are a significant cause of diarrheal disease in piglets globally. From birth, piglets rely on maternal antibodies in colostrum and milk to be passively protected from severe disease and mortality. Due to difficulty in propagating RVA and lack of cell culture systems for RVC, Natural planned exposure (NPE) remains one of the most common method in swine production to boost lactogenic immunity through pre-farrow exposure to live virus. However, the efficacy of NPE protocols in providing lactogenic immunity against RVA and RVC has not been investigated. There is also lack of serological tools to asses genotypic-antibody response to RVs. Most importantly, we do not know the factors driving high prevalence of RVC in neonatal piglets. The objectives of this dissertation are manifold. In chapter 2, a longitudinal study on a commercial farm assessed effect of different doses and timings of natural planned exposure (NPE) on generating passive lactogenic immunity in gilts/sows. We determined antibody response to different G and P-genotypes (G4, G5, P[7] and P[23]) of RVA using in-house optimized indirect ELISAs. We found that 3 doses of pre-farrow NPE administration in gilts results in significantly higher anti-RVA IgG and IgA levels in their colostrum and milk. Piglets born to group 1 gilts/sows had higher IgG titers at day 0 compared to other groups. Only two litters shed RVA prior to weaning ad carried a G11P[34] combination, which was different than the parent strains in the NPE material. RVC infection are more prevalent in neonatal piglets particularly in neonatal piglets, reasons of which are not completely understood. In the 3rd chapter, we sought to determine antibody response to two most prevalent G and P-genotypes (G6, P[5]) of RVC using in-house optimized indirect ELISAs and compare antibody responses to RVC shedding in pre-weaning piglets. We found that group 1 had higher colostral IgG and IgA titers compared to other groups. Interestingly, group 1 RVC antibody levels in day 0 piglet serum were either significantly (P[5]) or numerically (G6) higher than other groups. Higher group 1 colostrum and piglet serum levels suggest that 3 doses of NPE in gilts prior to farrowing was able to better stimulate maternal immunity than other treatment groups. However, none of the NPE doses were able to prevent RVC shedding by piglets in the farrowing room. A major goal of this work was to understand the antibody response to RVA and RVC, and how NPE shapes the genetic makeup of the RV strains in the piglet population. All 4 groups had significantly or numerically lower RVC colostrum antibody titers than RVA, irrespective of G and P-type. Piglet serum RVC IgA titers at day 0 were significantly lower than RVA titers. Low levels of colostrum and piglet serum antibody levels against RVC explains its higher prevalence in the neonatal piglets. The outer capsid proteins VP7 and VP4 of RVs are targets for the humoral immune response and they independently elicit neutralizing and protective immunity. In both Chapters 2 and 3 we observed that RVA and RVC IgG and IgA GMTs against VP4* were manifold higher compared to VP7 titers. To conclude, this work generates important data about humoral immune response to RVA and RVC NPE and lays ground for future research in the field of porcine RV immunology.
Keywords: Swine; Rotavirus; Antibody; Natural planned exposure; Lactogenic immunity; Sequencing